Pengalaman Mahasiswa Tuli di Ruang Komunal Universitas Mercu Buana - Harahap, Rachmita Maun; Lelo, Lelo (PLD UIN Sunan Kalijaga, 2020)
Deaf students have their characteristics in carrying out social interactions. Their distinctive social interactions influence the communal space setting on the Meruya campus of Mercu Buana University. This study uses a qualitative method and derives its approach from the emerging concept of deaf space architecture. Data were collected by mapping the behavior of deaf students, observation, and interviews. The results showed that behavior, activities, and spatial dimensions influenced the formation of communal spaces. Deaf students tend to rely on visual senses, which are controlled by spatial experiences in their activities. Deaf students tend to choose a gathering room that can provide easy access to move, which includes distance and density (deaf space), sensory reach, mobility, and the ability to provide high visibility to find out the presence of lecturers and an accessible parking area.[Mahasiswa Tuli memiliki karakteristik tersendiri dalam melakukan interaksi sosial. Interaksi sosial mereka yang khas mempengaruhi setting ruang komunal di kampus Meruya Universitas Mercu Buana. Penelitian ini menggunakan metode kualitatif dengan pendekatan deaf space. Data dikumpulkan melalui pemetaan perilaku mahasiswa Tuli, observasi, dan wawancara. Hasil penelitian menunjukkan bahwa pembentukan ruang komunal dipengaruhi oleh perilaku, aktivitas, dan dimensi ruang. Mahasiswa Tuli cenderung mengandalkan indra visual yang dipengaruhi oleh pengalaman ruang dalam beraktivitas. Mahasiswa Tuli cenderung memilih ruang berkumpul yang mampu memberikan kemudahan akses bergerak yang meliputi jarak dan kerapatan (deaf space), jangkauan sensori, mobilitas dan kemampuan memberikan visibilitas yang tinggi untuk mengetahui kehadiran dosen serta area parkir yang aksesibel.]